Citizenship education in Germany’s dual system of vocational education – a Bernsteinian approach - Höhns, Gabriela [Verfasser] (My University, 2025)
"This article uncovers potential spaces for citizenship education in regulated workplace learning in Germany’s dual system of vocational education. Following Rosvall and Nylund, it draws on Bernstein’s conceptual language to excavate realisations of ‘pedagogic rights’, conceived as the ability to think critically, a sense of belonging to a broader social basis than just a work group or a company, and a capacity to exert influence. Excerpts from interviews with dual system graduates reveal that a very strong or strong boundary between vocational school and company (no relation/contradiction or complementation) helped trainees/apprentices to think critically and to recognise the time- and context-relatedness of knowledge. Against expectations that learners in workplaces do not have a say, respondents recruited different forms of authority that they attributed to others, including other trainees/apprentices. Put differently, trainees/apprentices asserted authority, and they did so also in relation to their trainers. Thereby, they occupied spaces to influence the social basis of their learning. Bernstein’s concept ‘pedagogic culture’ helps to link these findings to the dual system’s broad basis, the social partners. This concept allows researchers to see that policies and legal prescriptions can make a difference to the possibilities for citizenship education in workplace learning." (author's abstract; BIBB-Doku)
Keywords: P 2.3 Auszubildende; 370; Auszubildender; Berufsausbildung; Lernort; Politische Bildung; Citizenship Education; Bernstein, Basil